Improving Basic Throwing and Catching Movements in Grade V Elementary School Students - Denni Sumartin; Sujarwo; Yasep Setiakarnawijaya; Oman Unju Subandi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This study aims to analyze the implementation of the game of throwing and catching to improve the learning outcomes of basic throwing and catching movements. This study was conducted on grade V students from one of the schools in Penjaringan District, North Jakarta City. With a total of 30 students who needed action. The design of this study used action research which was carried out through four stages, namely: planning, implementation, observation and evaluation. This study, which consisted of two cycles, used data collection techniques in the form of observation and throwing and catching test instruments which were then processed with descriptive statistics. The results of the study showed an increase of 80% in students’ throwing and catching movements from the pre-cycle to cycle II. Thus, the implementation of the game method in improving learning basic throwing and catching movements has a significant influence. This study recommends that further research can package games with more interesting game names and focus on the development of movement and student enthusiasm.